Electronic safety and soundness : securing finance in a new age - Glaessner, Thomas C.; Kellermann, Tom.; McNevin, Valerie (Washington, D.C. : World Bank, 2004)
The monograph defined electronic finance and electronic security and explains why these areas require attention. It provides examples of tradeoffs that may arise with respect to technological innovations, privacy, quality of service, and security in the design of an -security policy framework etc.
This is part of the World Bank Working Paper Series published to communicate the results of the Bank's ongoing research and to stimulate public discussion
Includes bibliographical references (p. 169-174).
rua 09/11/16
Loans
Keywords: Electronic funds transfers; Electronic security systems